The shame of reason in organizational change a Levinassian perspective - Van der Ven, Naud (Springer eBooks., 2011)
This book examines this question from the perspective of Emmanuel Levinas? treatment of rationality. There are close similarities between the Levinassian description of rational thinking and the role of managers in organizations. Rationality makes the world controllable yet is totalitarian in character. Likewise, managers make their businesses controllable, yet their planning and schemes create a totalitarian straitjacket.